2020
DOI: 10.33418/ataunikkefd.793821
|View full text |Cite
|
Sign up to set email alerts
|

Sanal Gerçekli̇k Teknoloji̇si̇ İle Sosyal Bi̇lgi̇ler Öğreti̇mi̇nde Kültür Aktarimi

Abstract: ÖzBu çalışmada sosyal bilgiler dersinde kültür aktarımını gerçekleştirmek için araştırmacı tarafından internet tabanlı sanal bir gerçeklik uygulaması (itSGU) geliştirilmiş ve bunun kültür aktarımı sürecine olan etkisi incelenmiştir. itSGU, ADDIE (analiz, tasarım, geliştirme, uygulama ve değerlendirme) öğretim tasarımı modeli baz alınarak oluşturulmuştur. Analiz aşamasında kültürün aktarımında yaşanan zorluklar etkili olmuştur. Aynı zamanda Google tarafından sanal gerçeklik teknolojisi için geliştirilen CardBoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
2
1
0
2
Order By: Relevance
“…When the virtual reality application was used in the science course, the students thought that the virtual reality learning environment attracted their attention and interest and made the science lessons funnier and more interesting than normal teaching. This result was consistent with the findings of previous studies (Kandemir & Demir, 2020;İneç, 2020). For instance, Gedik (2020) took the students' thoughts on the virtual reality application and concluded that the students' interest, engagement, and motivation for climate lessons taught by using virtual reality technology increased.…”
Section: Conclusion Discussion and Recommendationssupporting
confidence: 89%
See 2 more Smart Citations
“…When the virtual reality application was used in the science course, the students thought that the virtual reality learning environment attracted their attention and interest and made the science lessons funnier and more interesting than normal teaching. This result was consistent with the findings of previous studies (Kandemir & Demir, 2020;İneç, 2020). For instance, Gedik (2020) took the students' thoughts on the virtual reality application and concluded that the students' interest, engagement, and motivation for climate lessons taught by using virtual reality technology increased.…”
Section: Conclusion Discussion and Recommendationssupporting
confidence: 89%
“…The application of virtual reality technologies in the lessons helps to improve students' academic achievement significantly. In the literature review, it is seen that this study shows similar results to the studies carried out on virtual reality (Aktamış & Arıcı 2013;Chung, 2012;Dağdalan, 2019;Eryanto & Prestiliano, 2017;;Gedik, 2020;Hwang & Hu, 2013;İneç, 2020;Liou & Chang, 2018;Jou & Liu, 2012;Lee & Wong, 2014;Sarıçam, 2019;Sun, Lin & Wang, 2010;Tüzün et al, 2009). For example, according to the experimental research on virtual reality that was conducted by Sarıçam (2019), the students who used VRA believe that their imaginations developed during the virtual reality application process, and that they were constantly active throughout the process, resulting in more permanent knowledge.…”
Section: Conclusion Discussion and Recommendationssupporting
confidence: 81%
See 1 more Smart Citation
“…Tüm bu verilenlerin geçekleşmesi için öğretmenlere de oldukça önemli görevler düşmektedir. Bu konuda araştırmanın üçüncü bulgusunda katılımcılar, sosyal bilgiler öğretmenlerinin programın amaçlarını gerçekleştirebilmek için konuların gerçek hayatla ilişkilendirilmesi, öğretmenlerin sürekli olarak yeni bilgiler edinmeleri ve kendilerini geliştirmeleri, öğrenci merkezli bir eğitim anlayışına sahip olmaları ve olabildiğince farklı yöntem ve tekniklerin kullanabilmeleri gibi yapılandırmacı eğitimin temel ilkeleri ile uyumlu (İneç, 2020;Semerci ve Batdi, 2015;Er ve Aral, 2008;Koç, 2006;MEB, 2005;Wantson, 2001) olarak beklentilerini ifade etmişlerdir. Elde edilen bu bulguların alan yazında yer alan diğer çalışmalarla da desteklendiği söylenebilir (Yıldız ve Kılıç, 2018;Meral ve Şimşek, 2014;Ünal ve Çelikkaya, 2009;Doğanay ve Sarı, 2008).…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified
“…Sanal gerçeklik kullanımına ilişkin araştırmaların yeni yeni başladığı eğitim alanlarından biri de sosyal bilgilerdir (İneç, 2020;Gedik, 2020). Sosyal bilimlerin bir sentezi olan sosyal bilgiler, öğrencinin yakın çevresinden tüm dünyaya uzanan bir pencerenin açılmasında rol oynayan önemli bir derstir.…”
Section: Introductionunclassified